Subarachnoid versus General Anesthesia in Penile Prosthetic Implantation: Outcomes Analyses - Gerard D. Henry; Antonino Saccà; Elizabeth Eisenhart; Mario A. Cleves; Andrew C. Kramer (Advances in Urology)
The leading patient complaint during the perioperative period for penile prosthesis implantation is postoperative pain, while emesis and urticaria also affect the procedure’s perceived success. In analyzing surgical outcomes, assessment of the anesthetic for postoperative pain and side effects should be included. This paper retrospectively reviews 90 consecutive, primary inflatable penile prosthetic operations performed by a single surgeon at one private medical center. Fifty-seven patients were included in final analysis. Patients who had more than one procedure that day or who used chronic pain medication were excluded. The type and amount of each drug used for each respective side effect (within the first 24 hours after procedure) were compared to determine relative benefit. Twenty patients received general anesthesia (denoted herein as “GA”) and 37 received spinal (or also known as subarachnoid) anesthesia (denoted herein as “SA”). Patients receiving GA had significantly greater (P<0.0001) occurrence and amount of intravenous pain treatment than those receiving SA. Patients with SA required less intravenous pain medication and less treatment for nausea/emesis.